PERANAN PAJAK DAERAH DAN RETRIBUSI DAERAH PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET KABUPATEN ROKAN HULU - Is, Fitriyati (E-Journal Cano Ekonomos, 2013)
Local tax is obligatory contribution made by the individual or entity to region without compensation are balanced, which can be imposed, pursuant to the prevailing laws and regulations, used to finance local governance and local development. Revenue is all revenue from local taxes, levies, local wealth management result and regional development from revenues, especially those stemming from local taxesor levies. The local taxes and levies to help development activities revenue budget expenditures. Local governments are also digging a new local taxes annually. The research was conducted in Dinas Pendapatan Pengelolaan Keuangan dan Aset Kabupaten Rokan Hulu. This study uses descriptive data obtained subseqent highly structured and analyzed correctly by the theory relevant to the problems and then take a conclusion. From the results of this research note thet of the 10 types of local taxes under the authority of district/city government as stipulated in the laws of local taxes and levies, government Rokan Hulu only apply local taxes 9, and from 27 types of levies under the authority of district/city government as stipulated in the laws of local taxes and levie, the government Rokan Hulu implemented new 20 types retribution, meaning there are 7 types of retributions that have not been applied in Rokan Hulu.